Improving diagnostic models for forecasting the behavior of dams equipped with automated monitoring systems - Stefanyshyn, D. V. (ІТІГІП, 2016)
An approach to forecasting the behaviour of dams according to the data of instrumental observations with regard to capabilities of automated monitoring systems has been proposed. The approach is based on the use of situational and inductive models, where the situational models correspond to selective series of dynamics of observed data within limited time intervals and the inductive models which are constructed on model data derived from situational models simulate evolutions of diagnostic parameters.
Keywords: automated monitoring systems; dams; dependent and independent variable; instrumental observations; inductive and situational models; long-term and real-time forecasting; monotonic and non-monotonic data series of dynamics; 626/627 :621.7; 004.942; 519.25